Invasive treatment of atrial fibrillation. (July 2016) - Labedi, Mohamed; Marrouche, Nassir
Abstract : Purpose of review: The treatment of atrial fibrillation has experienced a significant evolution over the past two decades. Catheter-based ablation has become a first-line option in various guidelines. In this review, we highlight the recent multicenter ablation studies and the challenges facing this treatment modality. Recent findings: Improved efficacy and safety of an invasive treatment of paroxysmal and persistent atrial fibrillation with catheter ablation. Summary: Atrial fibrillation is a major health problem. Catheter ablation has become a standard of care in managing paroxysmal and persistent atrial fibrillation. This treatment modality, however, still faces major challenges, especially in patients presenting with persistent atrial fibrillation.